Morphology and mechanical performance between the skin surface of Rana dybowskii and Bufo gargarizans. Issue 3 (5th August 2021) - Li, Mo; Du, Chunyu; Wang, Jili; Gao, Zibo; Yang, Xiao; Chen, Donghui; Tong, Jin; Ren, Lili
Abstract: Anuran skin is a typical natural biomaterial with multifunctional features. A specific comparison of mechanical performance and morphology related to them was performed in the skin of Rana dybowskii and Bufo gargarizans using the tensile testing technique and morphological equipment. Rana dybowskii's skin has soft smooth surface covered by polygonal epidermal cells, while the Bufo gargarizans species has tough and uneven skin surface due to numerous verrucae structures. The collagen fibre bundles in lower dermis of Bufo gargarizans have wavelike organisation while the bundles of Rana dybowskii show a parallel arrangement. The mean elastic modulus of Rana dybowskii was nine times higher than that of Bufo gargarizans . This study clarified that the arrangement of collagen fibres play an important role in the strength and elasticity of skin material.